The perception of some members of parliament on the auditor general’s online dashboard disclosures / Ruhana Mohamad Zam - Mohamad Zam, Ruhana (2014)
This research is conducted as part of the contribution to the public sector auditing for the improvement of the Auditor’s General Reports in terms of isolating significant issues, disseminating information and also to integrate a good rapport between the government’s agencies and public. Technology has made browsing, analysing and reviewing the Auditor General’s Report more simple by clicking on the Auditor General's Online Dashboard. Areas to be covered in this study include the effectiveness and the extent of utilization of the Auditor General’s Online Dashboard disclosures. Therefore, this study will draw attention to the utilization of the Auditor General’s Online Dashboard disclosures from the public perspective and considering key issues for improvement. The aim of this study is (i) to investigate whether the Auditor General’s Online Dashboard disclosures manage to update the public on outstanding issues in the Auditor General's periodical reports; (ii) to determine whether the Auditor General’s Online Dashboard disclosures manage to promote transparency; (iii) to identify whether the Auditor General’s Online Dashboard disclosures manage to induce pressure to expedite resolution of issues; (iv) to ascertain whether the Auditor General's Online Dashboard disclosures manage to improve public perception on the Auditor General's roles and responsibilities; (v) to identify whether the Auditor General's Online Dashboard disclosures are able to provide satisfactory information to public; and to analyse suggestions from public for improvements the Auditor General's Online Dashboard disclosures. The research was carried out in 2 components, the first was a quantifiable investigation into the knowledge and experiences of staff to establish the main issue and in the second part, was obtaining a qualitative approach in order to gain a better understanding of some of the issues raised in the Questionnaires. Primary and secondary data were collected during the research processes. Primary data constituted of responses from interview, observation and questionnaires. Secondary data were internal publications from the National Audit Department of Malaysia such as articles, specific Guidelines or Standards of Procedure, Direct Instructions from the Auditor General of Malaysia, minutes of meeting and other related documents. Overall, the researcher believed that the set of respondents is a representative sample of public and stakeholders involved with the usage of the Auditor General’s Online Dashboard disclosures. Based on the analysis of the survey responses, the requirements of the research objectives are achieved and there is an alignment between the Audit Follow-up Division who is responsible to manage the Auditor General’s Online Dashboard disclosure with the requirements of Government Transformation Programme 2.0 included in 3rd initiative.